Karakterisasi dan Identifikasi Orthetrum sabina (Odonata: Lebullidae) di Lapangan Rusunawa Jerakah Purwoyoso Semarang: Karakterisasi dan Identifikasi Orthetrum sabina (Odonata: Lebullidae) di Lapangan Rusunawa Jerakah Purwoyoso Semarang - Muhammad Atourrohman; Malia Ulfah; Melin Septiani; Fina Idamatus Silmi; Ria Tri Utami; Siti Faza Malimah; Sinta Dewi Rahmawati; Afrizal Dwi Ananto; Bita Afriyati Dewi; Siti Mukhlisoh Setyawati (Litbang PWM Jawa Tengah, 2020)
Dragonfly or odonata is one of the biodiversity in Indonesia. Dragonfly act as bioindicator of aquatic ecosystem and predator for mosquitoes. Dragonfly habitat is usually in a watery place such as a river. This study purpose to identify and characteristic dragonflies in the Rusunawa field. The type of research used is qualitative descriptive research, which aims to determine the morphology of dragonflies with Orthetrum sabina type and to know the environmental factors that affect dragonfly breeding. The method used in this study is roaming, by searching for dragonflies in the Rusunawa field Jerakah. The dragonfly population found in the Jerakah field is mostly one of which is Orthetrum sabina which has a dark green thoracic characteristic with black lines on the lateral side and black legs. The abdomen is slim in black and white, the embellant is white and has transparent wings. The number of dragonflies is influenced by several factors, namely temperature, climate, air humidity, water ph and insecticide use.